2016
DOI: 10.18805/ijar.10277
|View full text |Cite
|
Sign up to set email alerts
|

Contagious ecthyma outbreak among goats at Nilgiri hills

Abstract: Contagious ecthyma is a highly contagious viral disease of sheep and goats, caused by Parapoxvirus. In the present outbreak over a range of 3 km radius in a hamlet near Ooty town in the Nilgiris hills, a total of 174 out of 194 non-descript goats were clinically affected with the symptoms of pyrexia (40°C), anorexia, depression, proliferative scab lesions on the skin around the mouth, oral commissures and nostrils. The morbidity rate was 89.7% without mortality. The symptoms were suggestive of contagious ecthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Contagious ecthyma is caused by the orf virus (ORFV), a member of the genus Parapoxvirus within the family Poxviridae that infects the skin and oral mucosa of ruminants, primarily sheep and goats, and causes painful vesicles, pustules, and proliferative lesions, typically around the mouth and nose ( 1 , 2 ). The morbidity rate is approximately 89% in sheep, and the disease has a substantial economic impact ( 1 , 3 ). The virus survives in scab material from ORFV lesions and can remain infectious for up to 15 years ( 4 , 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…Contagious ecthyma is caused by the orf virus (ORFV), a member of the genus Parapoxvirus within the family Poxviridae that infects the skin and oral mucosa of ruminants, primarily sheep and goats, and causes painful vesicles, pustules, and proliferative lesions, typically around the mouth and nose ( 1 , 2 ). The morbidity rate is approximately 89% in sheep, and the disease has a substantial economic impact ( 1 , 3 ). The virus survives in scab material from ORFV lesions and can remain infectious for up to 15 years ( 4 , 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…The disease is prevalent in worldwide and morbidity is very high usually ranges from 70-85 % causing huge economic losses (Peralta et al, 2015). In India, this disease has been reported from many areas (Mondal et al, 2006;Balakrishnan et al, 2017), however, so far no outbreak or any confirmed cases of the orf has been reported from this Islands. In the present study detail study has been carried out to study the outbreak of orf during different season and confirmation by PCR assay.…”
Section: Virus Gene Sequence (5'-3') Predicted Sizementioning
confidence: 99%